1999
DOI: 10.1523/jneurosci.19-19-08401.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neuron–Glia Signaling via α1Adrenoceptor-Mediated Ca2+Release in Bergmann Glial CellsIn Situ

Abstract: Adrenoceptors were among the first neurotransmitter receptors identified in glial cells, but it is not known whether these receptors meditate glial responses during neuronal activity. We show that repetitive nerve activity evoked a rise of intracellular calcium in Bergmann glia and neighboring Purkinje neurons of cerebellar slices of mice. The glial but not the neuronal calcium transient persisted during block of ionotropic and metabotropic glutamate receptors. In contrast, the glial calcium response was aboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 55 publications
2
76
1
1
Order By: Relevance
“…We found that blocking ␣1 adrenoceptors does not alter BG calcium signals, suggesting that the release of noradrenaline by locus ceruleus fibers is not required for BG calcium signals (Kulik et al, 1999). Similarly, the insensitivity of BG calcium signals to the blockade of NO synthase indicates that BG calcium signals do not require NO release (Matyash et al, 2001).…”
Section: Mechanisms Of Neuron-to-glia Signalingmentioning
confidence: 79%
See 2 more Smart Citations
“…We found that blocking ␣1 adrenoceptors does not alter BG calcium signals, suggesting that the release of noradrenaline by locus ceruleus fibers is not required for BG calcium signals (Kulik et al, 1999). Similarly, the insensitivity of BG calcium signals to the blockade of NO synthase indicates that BG calcium signals do not require NO release (Matyash et al, 2001).…”
Section: Mechanisms Of Neuron-to-glia Signalingmentioning
confidence: 79%
“…One study reported that BG calcium increases evoked by granule layer stimulation were blocked by the ␣1 adrenoceptor antagonist prazosin (Kulik et al, 1999), suggesting that activity in afferent fibers from the locus ceruleus trigger BG calcium signals. In contrast to these studies, calcium signals evoked by PF stimulation were not affected by prazosin (Fig.…”
Section: Mechanisms Underlying Neuron-to-glia Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in other brain regions or cell types have shown that a 1 adrenoceptors are coupled to PLC via a G-protein, and can increase the intracellular calcium concentration [Ca 2+ ] i by mobilizing Ca 2+ from intracellular stores, as well as by increasing the Ca 2+ influx (Schwinn et al, 1991;Wu et al, 1992;Cohen and Almazan, 1993;Lepretre et al, 1994;Kulik et al, 1999). However, certain effects of a 1A activation involve signaling pathways that are independent of PLC activation and intracellular Ca 2+ rise (Berts et al, 1999).…”
Section: Facilitation Of Gabaergic Transmission By a 1a Adrenoceptorsmentioning
confidence: 99%
“…a 1 -AR activation can increase the action potential-dependent inhibitory postsynaptic potentials in pyramidal neurons of the hippocampus by depolarizing surrounding inhibitory interneurons (Bergles et al 1996). a 1 -ARs may also affect many brain functions via non-neuronal mechanisms since they may be localized to glial cells (Kulik et al 1999). However, the lack of specific antibodies has also prohibited the determination of exact cell types that express a 1 -ARs.…”
mentioning
confidence: 99%